Sixty Years after the Magic Carpet Ride: The Long-Run Effect of the Early Childhood Environment on Social and Economic Outcomes - Gould, E. D.; Lavy, V.; Paserman, M. D. (Review of Economic Studies, 2011)
This paper estimates the effect of the early childhood environment on a large array of social and economic outcomes lasting almost 60 years. To do this, we exploit variation in the living conditions experienced by Yemenite children after being airlifted to Israel in 1949. We find that children who were placed in a more modern environment ( i.e. with better sanitary and infrastructure conditions) were more likely to obtain higher education, marry at an older age, have fewer children, and work at age 55. They were also more likely to be assimilated into Israeli society, to be less religious, and have more worldly tastes in music and food. However, these effects are found mainly for women and not for men. We also find an effect on the next generation—children who lived in a better environment grew up to have children with more education.